Solar light photodetectors based on nanocrystalline copper indium oxide/p-Si heterojunctions - Khusayfan, Najla M.; Al-Ghamdi, Ahmed A.; Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2016)
Transparent conducting thin films of nanocrystalline copper indium oxide (CuInO2) having delafossite structure were synthesized using the solegel spin-coating method. Partial substitution of In by Sn of varying percent weight realized films with the structure p-Si/CuIn1-xSnxO2 for x = 0, 0.01, 0.03, 0.05 and 0.07. Optical absorption measurements show that the films have transmittance between 45% and 90% for visible and near infrared wavelengths and a direct band gap energy in the 3.83 eV-3.93 eV range dependent on Sn content. The films exhibit a refractive index in the 1.2 to 1.4 range. Metalization of the composites using Al resulted in Schottky devices with the structure Al/p-Si/CuIn1-xSnxO2/Al which were investigated using direct current-voltage (I-V), photocurrent and impedance spectroscopy. The barrier heights showed low variance over illuminations and averaged 0.75, 0.72, 0.67, 0.74, 0.68 eV for x = 0, 0.01, 0.03, 0.05 and 0.07 of Sn. Capacitance-voltage (C-V) measurements suggest a continuous distribution of interface states over the frequency characterization range. The photocurrents were observed to increase with illumination intensity, with x = 0.03 showed the best photosensitivity over a wider range of applied reverse bias, the best photoresponse and the lowest series resistance (390 Omega). The obtained results suggest that the performance of the photodiodes can be tuned by adjusting Sn content. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Copper tin indium oxide; Photodiode; Photoresponse properties